Framing, truth telling and the problem with non‐directive counselling - Kirklin, D (BMJ Group, 2007)
In this paper several reasons as to why framing issues should be of greater interest to both medical ethicists and healthcare professionals are suggested: firstly, framing can help in explaining health behaviours that can, from the medical perspective, appear perverse; secondly, framing provides a way of describing the internal structure of ethical arguments; and thirdly, an understanding of framing issues can help in identifying clinical practices, such as non‐directive counselling, which may, inadvertently, be failing to meet their own stated ethical aims. The effect of framing on how individuals interpret information and how healthcare choices are influenced by framing are described. Next, the role of framing in ethical discourse is discussed with specific reference to Judith Jarvis Thomson's philosophical mind experiment about abortion and the violinist. Finally, the implications of this analysis are examined for the practice of non‐directive counselling, which aims at communicating information in a neutral, value‐free way and thereby protecting patient autonomy.